2010
DOI: 10.1021/bi101288y
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Energetics, and Dynamics of Binding Coactivator Peptide to the Human Retinoid X Receptor α Ligand Binding Domain Complex with 9-cis-Retinoic Acid

Abstract: Retinoid X receptors (RXRs) are ligand-dependent nuclear receptors, which are activated by the potent agonist 9-cis retinoic acid (9cRA). 9cRA binds to the ligand binding domain (LBD) of RXRs, and recruits coactivator proteins for gene transcription. Using isothermal titration calorimetry, the binding of a 13-mer coactivator peptide, GRIP-1, to the hRXRα-LBD homodimer complex containing 9cRA (hRXRα-LBD:9cRA:GRIP-1) is reported between 20° and 37 °C. ΔG is temperature independent (−8.5 kcal/mol), and GRIP-1 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(109 citation statements)
references
References 57 publications
5
104
0
Order By: Relevance
“…X-ray quality crystals of the hRXR␣-LBD⅐Targretin⅐GRIP-1 complex were obtained at 5-15% PEG 4000, 6 -12% glycerol, 0.1 M BisTris at pH 7.0. Both crystals had a P4 (3) 2 (1) 2 space group, which was the same as the crystals of the hRXR␣-LBD complex with 9cRA and GRIP-1 reported in our previous paper (12).…”
Section: Crystallization Of Hrxr␣-lbd Homodimers Bound To 9cuab30/supporting
confidence: 65%
See 3 more Smart Citations
“…X-ray quality crystals of the hRXR␣-LBD⅐Targretin⅐GRIP-1 complex were obtained at 5-15% PEG 4000, 6 -12% glycerol, 0.1 M BisTris at pH 7.0. Both crystals had a P4 (3) 2 (1) 2 space group, which was the same as the crystals of the hRXR␣-LBD complex with 9cRA and GRIP-1 reported in our previous paper (12).…”
Section: Crystallization Of Hrxr␣-lbd Homodimers Bound To 9cuab30/supporting
confidence: 65%
“…Crystallization of hRXR␣-LBD⅐9cUAB30⅐GRIP-1 and hRXR␣-LBD⅐9cRA⅐GRIP-1 homodimer complexes was similar to the method described previously (12) and those reported by Moras and co-workers (30). The crystals of hRXR␣-LBD homodimers with 9cUAB30 were obtained in a reservoir solution containing 5-10% PEG 4000, 2-5% glycerol, 0.1 M BisTris at pH 7.0.…”
Section: Crystallization Of Hrxr␣-lbd Homodimers Bound To 9cuab30/mentioning
confidence: 79%
See 2 more Smart Citations
“…In the LXRβ structure, different conformations of the ligand were also observed. A recent study of RXR complex to 9-cis retinoic acid and SRC-1 NR2 revealed a difference in the conformation of the 9-cis RA in the coactivator bound RXR (32).…”
Section: Discussionmentioning
confidence: 99%